Cysticercus tenuicollis of village sheep and goats in southwest Nigeria - Opasina, B.A. (1985)
Reports some observed cases of cysticercus tenuicollis seen at post-mortem examinations of West African Dwarf sheep (34) and goats (43) in South-West Nigeria; 23.7 percent of the sheep examined had single cysts in the peritoneum. All age groups were affected with 18.7 percent among sheep at post-weaning (up to 12 months), 33.3 percent in sheep aged 13 to 24 months and 26.7 percent in sheep of at least 24 months. Among the goats 11.6 percent of carcasses examined showed cysts. Only adult goats older than 24 months were infected.